Judas’s Other Pieces of Silver: The Biblical Denarius and the Art of Translation - Richardson, Gavin (KOINON: The International Journal of Classical Numismatic Studies, 2025)
This essay surveys translation approaches to the Gospel of John 12:5, where Mary of Bethany pours expensive oil upon the feet of Jesus as an act of devotion. Judas chastises Mary for wasting the oil, asserting that it could have been sold and the money given to the poor. The Greek expresses the value of the oil to be “300 denarii,” with the denarius being a small silver Roman coin. The value of the oil is expressed differently in a variety of English translations, with one common translation stating that it was worth “a year’s wages.” This essay examines translation approaches to the passage and argues that the literal reading of 300 denarii is important for understanding how the Gospel writer chooses to convey the character of Judas and the ethics of Jesus’s social world. The essay concludes with a broader consideration of the treatment of the denarius in the New Testament in contexts that involve the establishment of righteous priorities.